Tuntutan Uang Pesangon, Uang Penghargaan dan Uang Penggantian Hak melalui Pengadilan Hubungan Industrial atas Pemutusan Hubungan Kerja Secara Sepihak (Studi Kasus Putusan No: 219/Pdt Sus-Phi/2017/PN Mdn) - Yoga Aditya Prasetya; I Gusti Ngurah Adnyana (University of Merdeka Malang, 2022)
Termination of employment relations causes termination of employment relations due to a matter which results in the end of the rights and obligations between the worker/laborer and the entrepreneur. In terminating the employment relationship, sometimes a dispute arises, which is caused by the lack of understanding between the worker/laborer and the entrepreneur regarding terminating the employment relationship or because the entrepreneur only terminates the employment relationship but does not provide the rights that should be received by the worker such as severance pay, long service awards and compensation rights. Settlement related to layoffs because the employer only terminates the employment relationship but is not given the rights of workers that he/or the worker should get, then efforts can be made to resolve them in a bipartite manner, Mediation, Conciliation, Arbitration, and the Industrial Relations Court in accordance with the provisions in Law Number 2 of 2004 concerning Settlement of Industrial Relations Disputes. The results of this study can be drawn a conclusion, namely, how to obtain severance pay, long service pay, and compensation money. When a unilateral layoff occurs, it can be done in 2 ways, namely through litigation and non-litigation.